IMPLEMENTASI UNDANG UNDANG NOMOR 6 TAHUN 2014 (Studi Tentang Pengelolaan Alokasi Dana Desa Dalam Menunjang Pembangunan Pedesaan di Desa Sekaran Kecamatan Jatirogo Kabupaten Tuban ) - Sari, Anggita Oktavia Dewi Puspita; Indartuti, Endang; Soenarjanto, Bagoes (JPAP: Jurnal Penelitian Administrasi Publik, 2017)
IMPLEMENTATION OF LAW NUMBER 6 YEAR 2014(Study on the Management of Villages Fund Allocation in Supporting Rural Development in the Village Sekaran Jatirogo District Tuban Regency). One of the government's concern for the development of rural areas are by agreeing development budget that set out in Anggaran Pendapatan dan Belanja Daerah (APBD) called Alokasi Dana Desa (ADD). In Sekaran Village, sub district of Jatirogo, Tuban city, ADD was began in 2015, but the implementation indicated some problem that is the association of villages ability for planning, implementation and development in accordance with the potency that they have. Lack of administration report in accountability terms of the activities that are sourced from ADD. Lack of coaching by Upper Level Government technical institution that managing ADD with Facilitation and development team of ADD to the village officials.This research entitled as â€œImplementasi Undang Undang Nomor 6 Tahun 2014 (Studi Tentang Pengelolaan Alokasi Dana Desa Dalam Menunjang Pembangunan Pedesaan Di Desa Sekaran Kecamatan Jatirogo Kabupaten Tuban)â€. This research have two purposes, first is to determine the implementation of Alokasi Dana Desa in Sekaran village and second is to describe the Management Implementation of Alokasi Dana Desa to support the development of Sekaran Village, sub district of Jatirogo, Tuban city.This research is located in Sekaran Village, sub district of Jatirogo, Tuban city. Procedure of data collection done by interviews, observation and document research. The Informants of this research is the headman, treasurer, Government functionary, and some institutions as receiver of Alokasi Dana Desa. Data analysis was performed by data reduction, data presentation, and conclusion.This research using descriptive qualitative method. The result of the research shows that the Management Implementation of Alokasi Dana Desa in Efforts to Support the Development of Sekaran Village, sub district of Jatirogo, Tuban city goes well, seen from the communication factor, disposition and organizational structure.Â Keywords: implementation, management, and allocation of village funds.